Photoluminescence color-tuning with polymer-dispersed fluorescent films containing two fluorinated diphenylacetylene-type fluorophores - Kobayashi, Kazuki; Yamada, Shigeyuki; Yasui, Motohiro; Konno, Tsutomu (Beilstein Journal of Organic Chemistry, 2024)
The development of organic light-emitting devices has driven demand for new luminescent materials, particularly after the 2001 discovery of aggregation-induced emission. This study focuses on fluorinated diphenylacetylene-based luminescent molecules, revealing that specific molecular modifications can enhance fluorescence and achieve a wide range of photoluminescence colors. A simple and effective luminescence color-tuning method is proposed to investigate the photoluminescence behavior of two-component polymer dispersion films blended with two types of fluorinated diphenylacetylenes, namely blue- and yellow- or red-fluorescent fluorinated diphenylacetylenes. It is confirmed that if blue and green–yellow or yellow fluorophores are blended in appropriate ratios, a binary blend with color coordinates (0.20, 0.32) can be achieved, which approaches the white point of pure white emission. These findings contribute to the development of effective lighting and display devices as new white-light-emitting materials.
Keywords: energy transfer; fluorinated diphenylacetylenes; photoluminescence; polymer-dispersed films; white luminescence